Comparação entre os efeitos cardiovasculares da adrenalina e fenilefrina associadas à lidocaína e os efeitos da felipressina com a prilocaína durante a anestesia intrabucal em pacientes ASA I - Costa, Tatiany Bertollo Cozer Ribeiro da (2009)
The aim of this study was to evaluate cardiovascular effects by intrabucal infiltration of 1:100.000 epinephrine and 1:2.500 phenylephrine associated with 2% lidocaine compared with the effects by intrabucal infiltration of 0,03UI/ml felypressin associated with 3% prilocaine, during the surgery of third molars in ASA I patients. Eighteen volunteer patients of an academic oral surgery clinic were divided in two groups of nine patients. Group I (GI) evaluates the effects of epinephrine vs felypressin and in the group II (GII) evaluates the effects of phenylephrine vs felypressin. The cardiovascular parameters: systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR) and oxygen saturation (SatO2) were measured in pre, trans and post-operative periods as well as the number of cartridges used in the procedures. Statistical analysis (T-TEST) on the cardiovascular parameters demonstrated with significance that, for GI: the felypressin presented a HR average reduction in the postoperative period and a SatO2 averages reduction in the trans and postoperative periods. The average of used epinephrine cartridges vasoconstrictor was smaller than the average used with felypressin vasoconstrictor. For GII: the felypressin presented a SatO2 averages reduction in the postoperative period; SBP averages for patients submitted to phenylephrine increased in trans and postoperative periods; and DBP averages for patients submitted to phenylephrine increased in pre and transoperative periods.